SOFTWARE-DEFINED SDR RADIO SYSTEM - Ibodulloeva M.I; Korotkova Larisa Alexandrovna (International Journal of Innovations in Engineering Research and Technology, 2024)
The article presents software, which is one of the types of computer system support, along with technical (hardware), mathematical, informational, linguistic, organizational, methodological and legal support.